Designing an Entrepreneurial Marketing Model with a Sustainable Tourism Approach in the Post-COVID-19 Era - Paydarfard, Mehrab; Alizadeh Meshgani, Fatane; Azad, Naser (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The main objective of this research is to design an entrepreneurial marketing model with a sustainable tourism approach in the post-COVID-19 era. Methodology: The research methodology is applied in terms of purpose; qualitative in terms of method; and exploratory with an inductive philosophy in terms of data nature. The study participants were experts and managers in the tourism industry with more than seven years of experience and relevant educational backgrounds. A purposive sampling method and theoretical judgment were used to select participants for the interviews. Data collection was conducted in the field using semi-structured interviews based on a protocol. Data analysis was performed using the grounded theory method, Strauss and Corbin’s systematic approach, and open, axial, and selective coding with ATLAS.ti software. Findings: The coding results were categorized into five groups. Conclusion: The findings indicate that the causal factors influencing entrepreneurial marketing with a sustainable tourism approach in the post-COVID-19 era include customer orientation and resource leveraging; intervening factors include advertising and creativity; contextual factors include risk-taking, innovation orientation, and opportunity orientation; identified strategies include networking, tourism content creation, and value creation; and finally, the identified outcomes include cultural value of tourism and the historical significance of tourism.